Males as Identity Preservers of Indigenous Knowledge in Culinary Tradition During the Earth Alms Ceremony - Zulfatun Sofiyani; Ajeng Mustika Pratiwi (Digital Press Social Sciences and Humanities)
Culinary tradition is widely perceived as an activity predominantly performed by females. This assumption, however, contrasts with the culinary practice observed during the Earth Alms ceremony in the villages of Tlemang and Lukerjo, parts of Lamongan Regency. In this indigenous community, males are required to cook as part of social responsibility; in addition, serve as identities in preserving indigenous knowledge to pass on the culinary traditions at the Earth Alms ceremony across generations. Correlating to this, objectiveof the study is to explore the significance and pivotal role of males as identities in preserving indigenous knowledge in the Earth Alms culinary tradition. To achieve this, a qualitative with a phenomenological approach was employed by conducting direct interviews with informants, including men involved in the culinary tradition, as well as community members well-versed in the cultural and historical context of the Earth Alms ritual. Subsequently, the data were analysed through the theory of social construction of gender, examining how the role of men in this culinary tradition was formed and influenced by prevailing social norms. Another key aspectis that the social construction theory facilitated an understanding of how society constructs meaning of gender roles in the culinary tradition, while gender theory provided insights into the evolving role of men in preserving indigenous knowledge. Therefore, the study demonstrates that males serve an indispensable role in preserving indigenous knowledge in the culinary tradition of the Earth Alms ceremony, illustrating an attempt to sustain and maintain cultural involvement amidst ongoing social changes.